PERILAKU KONSUMEN DALAM PENGGUNAAN VOUCHER SHOPEE - DENOK WAHYUDI SETYO RAHAYU (Universitas Islam Balitar, 2022)
Consumer behavior is something that becomes a habit for consumers in shopping. Producer or seller knowledge on consumer behavior can provide positive value for the seller. The purpose of this research is to find out consumer behavior with the existence of Shopee vouchers. The research data was obtained through observations on the online shopping application Shopee within 3 months of the study. The voucher used is free shipping and xtra cashback. Analysis of research data using data reduction, data presentation, and drawing conclusions. The results of the study show that the use of Shopee vouchers leads to consumer behavior, namely the tendency to shop, because these vouchers provide benefits for consumers.